2021
DOI: 10.1126/sciadv.abg8205
|View full text |Cite
|
Sign up to set email alerts
|

RNA polymerase II is required for spatial chromatin reorganization following exit from mitosis

Abstract: Following exit from mitosis, RNA Pol II is required for reestablishing 3D genome folding by loading cohesin complexes onto DNA.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
45
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 82 publications
7
45
1
Order By: Relevance
“…Acute ablation of any of the three RNA polymerases with an auxin-inducible degron had negligible effects on any feature of genome architecture, including TADs (Jiang et al, 2020). The resolution of this study may not have been high enough to discern subtle effects, and a similar experimental approach showed that whereas interphase chromatin was indeed largely unaltered, resetting of TADs just after mitosis was affected by loss of RNA polymerase II (Zhang et al, 2021). As an alternative means of testing the direct effect of transcription on chromatin topology, another study used CRISPR-activation (CRISPRa; Gilbert et al, 2013) to ectopically induce two specific genes in ESCs: Sox4 and Zfp608 (Bonev et al, 2017).…”
Section: Introductionmentioning
confidence: 98%
“…Acute ablation of any of the three RNA polymerases with an auxin-inducible degron had negligible effects on any feature of genome architecture, including TADs (Jiang et al, 2020). The resolution of this study may not have been high enough to discern subtle effects, and a similar experimental approach showed that whereas interphase chromatin was indeed largely unaltered, resetting of TADs just after mitosis was affected by loss of RNA polymerase II (Zhang et al, 2021). As an alternative means of testing the direct effect of transcription on chromatin topology, another study used CRISPR-activation (CRISPRa; Gilbert et al, 2013) to ectopically induce two specific genes in ESCs: Sox4 and Zfp608 (Bonev et al, 2017).…”
Section: Introductionmentioning
confidence: 98%
“…Two recent studies shine new light on how transcription modulates proper domain formation in the chromatin. In the first study, Pol II was acutely depleted in human DLD-1 cell line to assess its contribution to genome folding [ 122 ]. Hi-C analysis of chromatin folding on G1-sorted cells after extended depletion (14 hours) revealed only a mild disruption of TADs.…”
Section: Transcription On a Megabase Scalementioning
confidence: 99%
“…Importantly, reducing H3K27ac with a new selective inhibitor of the catalytic subunit of CBP/p300 impairs gene reactivation during mitotic exit (even if inhibition only takes place in anaphase/telophase), indicating H3K27ac recovery during this time period is important for reactivation [ 11 , 12 ]. Interestingly, depleting mitotic RNA pol II leads to reduced H3K27ac levels and cohesin loading in early G1, hinting at a possible link between canonical TF activity and H3K27ac deposition during M-G1 [ 72 ]. Altogether, these observations also cement the importance M-G1 time-window may have for cell identity maintenance and cell fate changes.…”
Section: Tf Activity and Waves Of Transcriptional Reactivation During...mentioning
confidence: 99%